Biocultural restoration in Hawaiʻi also achieves core conservation goals - Kawika B. Winter (Resilience Alliance, 2020)
Biocultural approaches to restoration have demonstrated multiple benefits for human communities, but the ecological benefits and trade-offs involved have received little attention. Using a case study from Hawaiʻi, we examined if forest restoration aimed at reviving and maintaining cultural interactions with the forest is compatible with other priority conservation metrics. We identified species of high biocultural value for an Indigenous (Native Hawaiian) community, and then tested if these species also have high conservation value in terms of their biogeographic origin, ability to support native wildlife, and ability to persist independently within the restored context. Additionally, we tested if an assemblage of species with high biocultural value can also support high functional trait diversity. We found bioculturally important species to have high conservation values for all metrics tested, except for the ability to conserve rare or endangered endemic species. However, a broader application of biocultural conservation, such as the revival of the "sacred forest" concept, can address this priority as part of a mosaic of different species assemblages and levels of access. We also found that biocultural value may, at least in part, be a function of coevolutionary time: the length of time over which a community has interacted with a given species. Given that forests are invaluable to many Indigenous communities and, given the existential threats many of these communities currently face, we suggest that forests containing species assemblages of high biocultural value, such as those in Hawaiʻi, be considered as critical cultural habitat.